Capparaceae endémicas del Perú - Monsalve, Christhian (2006)
The Capparaceae are represented in Peru by six genera and 48 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mainly shrubs and low trees. Here we recognize five endemic species in three genera. These endemic species grow in the Humid Lowland Amazonian Forests and Very Humid Premontane Forests regions, between 350 and 1600 m elevation. We applied IUCN categories and criteria to three endemic species. No endemic Capparaceae have been recorded from Peru’s protected areas system.